Sustainable marketing strategy: building an eco-friendly brand - Ismail Razak (BIOS: Jurnal Informatika dan Sains, 2024)
Increasing consumer awareness of environmental and social issues is encouraging companies to adopt a more sustainable approach in their marketing. This research will focus on marketing practices that are effective in creating a positive brand image in the eyes of consumers, while maintaining environmental integrity. Therefore, the aim of this research is to investigate and analyze sustainable marketing strategies used in building environmentally friendly brands. This research uses a qualitative approach with descriptive methods. The research results show that implementing sustainable marketing strategies has a positive impact on brand image. By prioritizing transparency, the use of sustainable labels and certifications, product innovation, and participation in environmental initiatives, companies can build strong relationships with increasingly environmentally conscious consumers. Consumer education campaigns about the benefits of sustainable products have also proven effective in forming positive perceptions. Sustainable business practices, such as sustainability in the supply chain and waste reduction, demonstrate a real commitment to environmental responsibility. These results provide a basis for recommending the implementation of sustainable marketing strategies as an important step for companies wishing to strengthen their brand image in a sustainability context.